NRG1/ErbB2 axis regulated mitochondrial function and antioxidant enzymes of neural stem cells in the cochlear nucleus partially through PGC-1α. (1st January 2023) - Wang, Jian; Wei, Li; Tian, Keyong; Xu, Min; Chen, Xiaodong; Chen, Fuquan; Zha, Dingjun; Xue, Tao
Highlights: ErbB2 knockdown reduced the antioxidant enzymes in NSCs treated by NRG1. ErbB2 knockdown suppressed expression of mitochondrial biogenesis-associated genes. PGC-1α signaling mediated the effects of the NRG1/ErbB2 axis in NSCs. Abstract: Neuregulin-1 (NRG1)/erythroblastic leukaemia viral oncogene homologues 2 (ErbB2) pathway had been implicated in promoting differentiation and suppressing apoptosis of neuronal stem cells (NSCs) isolated from cochlear nucleus. In the current study, we aimed at determining the effects of NRG1/ErbB2 on mitochondrial (mt) function of NSCs. As expected, NRG1 increased the expression of mitofusin (Mfn) 1 and Mfn2 and decreased the expression of mitochondrial fission protein 1 (Fis1) and dynamin-related protein 1 (Drp1). However, after ErbB2 knockout, Mfn1 and Mfn2 expression decreased while Fis1 and Drp1 increased. Moreover, the increased mtDNA copy number and intracellular ATP level, elevated ATPase activities as well as decreased lactate production induced by NRG1 were partially reversed by ErbB2 knockout. Additionally, NRG1 treatment increased the activities of catalase, superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and upregulated the protein expression of catalase, manganese superoxide dismutase (MnSOD), peroxisome proliferator-activated receptor-γ coactlvator-1α (PGC-1α), nuclear respiratory factor 1 (NRF1) and transcription factor A, mitochondrial (TFAM), which were also reversed by ErbB2 knockout. Furthermore, PGC-1α overexpression partially reversed the above effects of ErbB2 knockout. In conclusion, these findings suggest that the promotion of mitochondrial function of NRG1/ErbB2 axis is at least in part mediated by PGC-1α in NSCs from cochlear nucleus.